Gamification in Mobile Learning Enhancing Engagement and Retention through Interactive Design - Paudel, Bishal; Shrestha, Sushma (Journal Mobile Technologies (JMS), 2025)
This study investigates the effectiveness of gamification in mobile learning environments in enhancing student engagement and knowledge retention within higher education institutions in Nepal. A mixed-methods design was adopted, combining quantitative and qualitative analyses among 120 undergraduate students from Tribhuvan University and its affiliated colleges. The experimental group used gamified mobile applications incorporating points, badges, leaderboards, and collaborative challenges, while the control group relied on standard mobile learning tools. Statistical results revealed substantial gains in engagement (from 3.2 to 4.3 on a five-point scale) and retention (from 62.4% to 78.6%) among students exposed to gamified platforms, with differences confirmed as significant (p < 0.001). Thematic analysis indicated that gamification fostered motivation, reduced learning stress, and encouraged teamwork through interactive experiences. These findings suggest that gamified mobile learning not only improves academic outcomes but also promotes social interaction and sustained participation, particularly in Nepal’s multilingual and culturally diverse classrooms. The study concludes that incorporating gamification into mobile learning can create a more active, inclusive, and enjoyable educational environment, supporting long-term learner engagement and cognitive development.